2016
DOI: 10.4103/1319-2442.174088
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies and socio-demographic characteristics among Jordanian caregivers of patients receiving hemodialysis

Abstract: Individuals who care for family members receiving chronic hemodialysis (HD) are likely to experience burdens that may adversely impact their patients. Effective coping strategies are shaped by various factors, including sociodemographic characteristics. To assess the relationship between caregivers and their patients, we studied 225 family-member caregivers of chronic HD patients through answering the Ways of Coping Questionnaire-Revised. Sociodemographic data, including caregiver age, gender, educational leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 2 publications
1
33
0
4
Order By: Relevance
“…In the study conducted by Eman Alnazly, caregivers who are spouses, fathers, mothers and brothers of the patients feel less care burden and also feel more comfortable because caregivers feel a sense of commitment towards the person. In this situation, their sense of responsibility as caregivers forms part of their coping strategy . Similarly, in the study by Avşar et al , caregivers of haemodialysis and renal transplant patients who have greater kinship ties with the patients were found to feel more satisfied, score their quality of life as higher and have better sleep quality because of their sense of responsibility towards patients, thus promoting greater acceptance of their situation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In the study conducted by Eman Alnazly, caregivers who are spouses, fathers, mothers and brothers of the patients feel less care burden and also feel more comfortable because caregivers feel a sense of commitment towards the person. In this situation, their sense of responsibility as caregivers forms part of their coping strategy . Similarly, in the study by Avşar et al , caregivers of haemodialysis and renal transplant patients who have greater kinship ties with the patients were found to feel more satisfied, score their quality of life as higher and have better sleep quality because of their sense of responsibility towards patients, thus promoting greater acceptance of their situation.…”
Section: Discussionmentioning
confidence: 88%
“…Eman Alnazly (11) states that in Muslim culture, religious teachings encourage family members to take care of chronically ill patients at home, and patients are highly respected and valued by their family members; moreover, the results of his study indicate that religious beliefs highly influence caregivers' acceptance of their situation. According to the results of Saffari et al (42), in Muslim patients undergoing dialysis, spiritual strategies are often used and based on cultural and religious beliefs, leading to greater acceptance of their situation and improving their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the present study, family support is indicated as the most important one (28). Family members play an increasingly vital role in improving self-care behaviours and facilitating patients’ adjustment to illness (29). Support by spouses can be a source of strength whereas support from friends is significant to retired hemodialysis individuals (19).…”
Section: Discussionmentioning
confidence: 99%
“…11 Several studies have shown that CKD patients use a variety of coping strategies when dealing with their disease. 9,12,13 Dehkordi and Shahgholian 9 examined coping strategies and found patients used emotion-focused coping strategies more to adapt with the disease compared to problem-focused coping strategies. 9 Similarly, Parvan et al reported that a majority of patients used emotion-oriented coping strategies to deal with stress factors.…”
Section: Introductionmentioning
confidence: 99%